Ultrasound diagnosis of lateral digital extensor muscle, tendon, and synovial sheath alterations in Colombian creole horses with clinical signs of tarsus hyperflexion - Vega, Fernando E.; Martínez, José R. (Revista Colombiana de Ciencias Pecuarias, 2018)
Background: Tarsus hyperflexion alters locomotion biomechanics in horses. This alteration is of frequent presentation in the Colombian creole horse (CCH). Objective: To determine the echographic alterations of lateral digital extensor (LDE) muscle, tendon, and synovial sheath in CCH with clinical signs of tarsus hyperflexion. Methods: Thirty horses were divided into two groups: 15 healthy horses with no history of locomotion defects (Group 1; control), and 15 horses with clinical signs of tarsus hyperflexion (Group 2). A cross-sectional and a longitudinal echocardiographic examination of the LDE muscle and tendon was performed in all horses, and a histopathological study was performed only to Group 2. Results: 86.7% of the horses showed echographic alterations, with 53.4% showing signs of adhesions in the LDE muscle and tendon in the lateral surface of the hock, where it crosses the tarsus. 33.3% presented increased tendon sinovial sheath fluid. 13.3% showed no echographic alterations and 53.3% presented histopathological alterations. Conclusion: These findings may be related to the presentation of tarsus hyperflexion that could characterize the classic stringhalt in CCH.